Utilisation of Intermediate Care Units: A Systematic Review - Joost D. J. Plate; Luke P. H. Leenen; Marijn Houwert; Falco Hietbrink (Critical Care Research and Practice)
Background. The diversity in formats of Intermediate Care Units (IMCUs) makes it difficult to compare data from different settings. The purpose of this article was to describe and quantify these different formations and utilisation. Methods. We performed a systematic review extracting geographic location, nomenclature used, admitting specialties, open (admitting specialist in charge) or closed (intensivist/generalist in charge) management format, location in hospital, number of beds, nursing workload, medical staff to patient ratios, and modalities—possibilities and limitations—implemented. Results. Nomenclature used was High Dependency Unit (56.8%) or Intermediate Care Unit (24.3%), with the latter one increasingly being used recently. The median number of beds was 6 (IQR 4–10). Location (p<0.001) and admitting specialties (p=0.03) were related to the management format. IMCUs integrated or adjacent to Intensive Care Units were more often capable of using single vasoactive medication (p=0.025). The mean nurse to patient ratio was 1 to 2.5. Conclusions. IMCUs often have a specific task in a hospital, which is reflected in location, format, and utilisation. The management format depends on location and admitting specialist while incorporated supportive treatment modules reflect its function. Common IMCU denominators are continuous monitoring and respiratory support, without mechanical ventilation and multiple vasoactive medications.